A study on ulinastatin in preventing post ERCP pancreatitis - Vedamanickam, R.; Kumar, Vinoth; ., Hariprasad (International Journal of Advances in Medicine, 2017)
Background: Pancreatitis remains the major complication of endoscopic retrograde cholangiopancreatography (ERCP), and hyperenzymemia after ERCP is common. Ulinastatin, a protease inhibitor, has proved effective in the treatment of acute pancreatitis. The aim of this study was to assess the efficacy of ulinastatin, compare to placebo study to assess the incidence of complication due to ERCPP procedure. Methods: In this study a randomized placebo controlled trial, patients undergoing the first ERCP was randomizing to receive ulinastatin one lakh units (or) placebo by intravenous infusion one hour before ERCP for ten minutes duration. Clinical evaluation, serum amylase, ware analysed before the procedure 4 hours and 24 hours after the procedure. Results: Total of 46 patients were enrolled (23 in ulinastatin and 23 in placebo group). The incidence of Hyper enzymemia is lower in ulinastatin group (13 %) than in placebo group (30.4%). Conclusions: Prophylactic short-term administration of ulinastatin one lakh units intravenously, one hour before ERCP procedure is effective when compared to placebo infusion.